2020
DOI: 10.3390/ani10040656
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Are Consumers’ Perception and Acceptance of Alternative Meat Production Systems Affected by Information? The Case of Cultured Meat

Abstract: The global meat production system is currently under pressure, particularly for its environmental and animal wellbeing impacts, as well as for the increasing protein demand worldwide. In this regard, cultured meat is currently a hot topic in the industrial, political, and societal arenas, revealing itself as the potential relief for the issues above. However, its high degree of novelty may hamper the extent of consumers’ acceptance. This research assesses for which beliefs concerning intrinsic attributes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 76 publications
6
42
2
Order By: Relevance
“…Zhang, Li and Bai [33] found that providing additional information about the environmental benefits of cultured meat increased acceptance amongst urban Chinese consumers. Mancini and Antonioli [18] found that providing additional positive information about cultured meat significantly increased the various measures of acceptance including the willingness to buy, but not the willingness to try.…”
Section: Increasing Acceptancementioning
confidence: 99%
See 4 more Smart Citations
“…Zhang, Li and Bai [33] found that providing additional information about the environmental benefits of cultured meat increased acceptance amongst urban Chinese consumers. Mancini and Antonioli [18] found that providing additional positive information about cultured meat significantly increased the various measures of acceptance including the willingness to buy, but not the willingness to try.…”
Section: Increasing Acceptancementioning
confidence: 99%
“…There is evidence that consumers do care about the animal suffering of meat production; Weinrich et al [31] found that perceiving cultured meat as an ethical product was the strongest driver of purchase intent in a representative German sample, whilst Bryant et al [21] report that the ethical evaluation of cultured meat was especially important in India. Mancini and Antonioli [18] found that extra information improved the perceptions of the animal welfare implications of cultured meat, except for vegetarians.…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations